Properties and Advantages of the Quasi-Z-Source Inverter for DC-AC-Conversion for Electric Vehicle Application - Beer, Eva Katharina; Piepenbreier, Bernhard (VDE Kongress 2010, 2010)
This paper presents features and advantages of the DC-AC quasi-Z-source inverter (qZSI) for use in electric vehicles. The qZSI with continuous input current and its wide range boosting ability is suitable for this application where a three-phase induction motor should be supplied from a lower battery voltage. At first, the theoretical circuit analysis will be given and on this basis dimensioning equations for the components are derived and verification is carried out by means of simulation. Lastly, experimental results and measurements made with a qZSI test setup will be given.
UnivIS-Import:2015-04-16:Pub.2010.tech.IE.LEEAS.proper
Keywords: Converter circuit; DC-AC power conversion; Inverters; Voltage-fed inverter; Z-source